The Influence of Corticosteroid Injections on Postoperative Outcomes of Carpal Tunnel Release: A Systematic Review - Ali Kumaş; Milly van de Warenburg; Tinatin Natroshvili; Marius Kemler; Mahyar Foumani (Archives of Plastic Surgery, 2023)
Background Carpal tunnel syndrome can be treated with corticosteroid injections (CIs) and surgery. In this systematic review, the influence of previous CI on different postoperative outcomes after carpal tunnel release is evaluated.